LITERASI MEDIA DIGITAL BERBASIS INDIVIDUAL COMPETENCE FRAMEWORK PADA ANGGOTA MAJELIS TAKLIM KOTA PALEMBANG PENGGUNA WHATSAPP - Nurly Meilinda; Krisna Murti; Novaria Maulina (Metacommunication: Journal of Communication Studies, 2019)
This study aims to determine the level of digital media literacy based on the individual competence framework in member of Majelis Taklim of Palembang City. This study uses a quantitative approach with a survey method based on the framework of the individual competence framework of the Europian Commission. This study involved 80 research respondents from members of the Taklim Assembly in Palembang City. the individual competence of Taklim members in using the WhatsApp application are in the advanced category, with details as follows: use skills are in the advanced category, critical understanding is in the advanced category, communicative abilities are in the advanced category. The advance category means that members of the Taklim assembly in the city of Palembang have been very active in using media, they are also aware and interested in various regulations that affect the use of digital media, especially WhatsApp. Respondents have deep knowledge of techniques and languages and can communicate and create messages. In the social field, respondents have been able to activate group collaboration that allows him to solve problems. The factors that encourage respondents to use WhatsApp are environmental factors and individual factors. Environmental factors are encouragement from family members and people around the respondents, while individual factors are a sense of motivation to be able to socialize and add information to themselves.